„Die höfischen Künste in ‚Flore und Blanscheflur‘ und ‚Apollonius von Tyrland‘“ - Egidi, Margreth (Interartifizialität. Die Diskussion der Künste in der mittelalterlichen Literatur (Sonderh. der ZfdPh 128))

„Verborgene Heiligkeit. Legendarisches Erzählen in der Alexiuslegende“ - Egidi, Margreth (Literarische und religiöse Kommunikation in Mittelalter und Früher Neuzeit [DFG-Symposion 2006])

Jean Piaget, Die Entwicklung der physikalischen Mengenbegriffe beim Kinde: Erhaltung und Atomismus - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Jean Piaget, Das Erwachen der Intelligenz beim Kinde - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Early Top-Down Influences in Control of Attention: Evidence from the Attentional Blink - Hilkenmeier, Frederic; Tünnermann, Jan; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
The relevance of top-down information in the deployment of attention has more and more been emphasized in cognitive psychology. We present recent findings about the dynamic of these processes and also demonstrate that task relevance can be adjusted rapidly by incoming bottom-up information. This adjustment substantially increases performance in a subsequent task. Implications for artificial visual models are discussed.
Keywords: visuo-spatial attention; top-down control; task relevance; artificial visual attention; attentional blink

Attention Speeds Up Visual Information Processing: Selection for Perception or Selection for Action? - Weiß, Katharina; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Attention speeds up information processing. Although this finding has a long history in experimental psychology, it has found less regard in computational models of visual attention. In psychological research, two frameworks explain the function of attention.Selection for perception emphasizes that perception- or consciousness-related processing presupposes selection of relevant information, whereas selection for action emphasizes that action constraints make selection necessary. In the present study, we ask whether or how far attention, as measured by the speed-up of information processing, is based on selection for perception or selection for action. The accelerating effect was primarily based on selection for perception, but there was also a substantial effect of selection for action.
Keywords: visuo-spatial attention; prior entry; selection for action; selection for perception

What you see is what you set – the position of moving objects - Priess, Heinz-Werner; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Human observers consequently misjudge the position of moving objects towards the direction of motion. This so called flash-lag effect is supposed to be related to very basic processes such as processing latencies in the human brain. In our study we show that this effect can be inversed by changing the task-set of the observer. A top-down change of the observers attentional set leads to a different perception of otherwise identical scenes. Cognitive theories regard the misperception of the moving object as an important feature of attention-mediated processing, because it reflects the prioritized processing of important objects.

China's provincial disparities and the determinants of provincial inequality - Gries, Thomas; Redlin, Margarete (Journal of Chinese Economic and Business Studies)

My Mother: My Best Friend? Adults’ Relationships with Significant Others Across the Lifespan - Buhl, Heike M. (Journal of Adult Development)
In order to investigate the significance of adults’ relationship to their parents, this relationship is compared to relationships with siblings, friends, partners, and children. German adults (N = 902) between the ages of 20 and 86 completed the Network of Relationships Inventory (Furman and Buhrmester 1992). Participants felt most supported by their partners, followed by their children, mothers, friends, fathers, and siblings. Conflicts were more frequently found within the family (especially with the partner, followed by children, mothers, fathers, and siblings) than with friends. Except for partner relationships, both conflict and support decreased with age. Concerning relative power within their relationships, partners, mothers, and siblings are seen as equals, friends and especially fathers are perceived as more powerful, and children as less, yet increasingly powerful. Regarding all relationship types and relationship qualities, the differences between women and men were small.
Keywords: Family; Friends; Support; Conflict; Power

Zusammenhänge zwischen der Fähigkeit zur Perspektivenübernahme und dem Textverstehen im Vor- und Grundschulalter - Buhl, Heike M.; Möller, Franziska; Oebser, Manuela; Stein, Freia; Noack, Peter (Diskurs Kindheits- und Jugendforschung)
Im vorliegenden Beitrag wird der Zusammenhang zwischen der Fähigkeit zur Perspektivenübernahme und sinnverstehendem Lesen dargestellt. Auf der Grundlage von Arbeiten zum Textverstehen sowie zu Perspektivenübernahme und Theory of Mind wurde ein positiver Zusammenhang zwischen Perspektivenübernahmefähigkeit und Textverstehensleistung erwartet. Diese Hypothese wurde an zwei Stichproben unterschiedlichen Alters geprüft: In der ersten Studie beantworteten 37 Vorschulkinder Fragen zu vorgelesenen Geschichten sowie Perspektivenübernahme-Aufgaben. Zwischen den Bereichen fand sich eine deutliche positive Korrelation, die bei Kontrolle der Intelligenz erhalten blieb. An der zweiten Studie nahmen 69 Grundschulkinder der dritten Jahrgangsstufe teil, die Texte lasen und Aufgaben dazu wie auch zur Perspektivenübernahme bearbeiteten. In dieser Stichprobe fand sich der erwartete Zusammenhang ausschließlich in der Teilgruppe der guten Leser. Er blieb bei Kontrolle der Intelligenz erhalten. Die Ergebnisse werden auch in Hinblick auf die Förderung der Lesekompetenz diskutiert.
Keywords: Textverstehen; Lesekompetenz; Perspektivenübernahme; Theory of Mind; Kindesalter

Wilhelm Worringer: Abstraktion und Einfühlung - Öhlschläger, Claudia (Kindlers Literatur Lexikon. Dritte, völlig neu bearbeitete Auflage. 18 Bände inkl. einem Registerband)

Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert

"Wortschatzsammler" im Unterricht: Entwicklung und Evaluation eines strategieorientierten, unterrichtsintegrierten Förderkonzepts - Motsch, H.J; Brüll, T (Vierteljahresschrift für Heilpädagogik und ihre Nachbargebiete)

Liebes-Geschichten: Von Petrarcas Amorallegorien zu Fontenelles Allegorisierungen der Liebe - Steigerwald, Jörn (Comparatio. Zeitschrift für Vergleichende Literaturwissenschaft 1 / 1)

Narration und Ethik. Bd. 1 der Reihe „Ethik-Text-Kultur“

Faszination des Ornamentalen: Zur Tiefe der Oberflächenästhetik in Fotografien Andreas Gurskys - Öhlschläger, Claudia (Faszination. Historische Konjunkturen und heuristische Tragweite eines Begriffs)

Die Distanz bewohnen ́. Zur Ethik der Scham bei Adalbert Stifter - Öhlschläger, Claudia (Jahrbuch der Deutschen Schillergesellschaft LI II/2009)

Lemma Christian Thomasius: Von der Nachahmung der Franzosen - Steigerwald, Jörn (Poetiken. Autoren – Texte – Begriffe)

Lemma D.A.F. de Sade: Idée sur les romans - Steigerwald, Jörn (Poetiken. Autoren – Texte – Begriffe)

Verräumlichte Augen-Blicke. Narrative Visualisierungsstrategien in Mme de Staëls „Corinne“ und Goethes „Wahlverwandtschaften“ - Steigerwald, Jörn (Lesbarkeit der Romantik)